Techno-economic and environmental analysis of grid connected hybrid wind/photovoltaic/biomass system for Marmara University Goztepe campus - TERZİ, ÜMİT KEMALETTİN (TAYLOR & FRANCIS INC, 2020)
This study focuses on techno-economic and environmental feasibility study of a hybrid grid connected wind/PV/biomass energy system for Marmara University Goztepe Campus in Istanbul. HOMER software is used to determine the optimum size of the equipment, based on the geographical and meteorological data of the campus. According to the simulation results, the energy system with the minimum net present cost (NPC) and cost of energy (COE) is chosen as the optimum system. Besides, this study aims to reduce greenhouse gas emissions, polluting the air by using renewable resources. Because of negative impacts of the fossil fuels on human health and environment, all the energy sources for this system are renewable energies which have less pollution. In the simulation, PV, wind, and biomass energy resources are used, but the optimum hybrid energy system is determined as grid connected wind/biomass system consisting of 1000 kW grid, 1000 kW biomass generator, and 1500 kW wind turbine. The NPC of the optimum system is calculated as $5.612.501 while the COE is 0,067$/kW. The system also decreases the emissions of greenhouse gases.
Keywords: Hybrid renewable energy systems; techno-economic feasibility; HOMER; renewable energy resources; ENERGY SYSTEM; WIND